(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Alstonia venenata R. Br. belonging to the family Apocynaceae is a tall evergreen shrub distributed throughout Peninsular India. Stem-bark, root-bark, fruits and leaves are used by many tribal communities and also in Ayurveda. The study investigates the phytochemical composition of hexane, butanol, methanol and water extracts of Alstonia venenata fruits and flowers as well as the TLC profile of hexane extracts of fruits and flowers. Quantitative data of the wet and dry weight, yields from different solvent fractions and percentage yields were noted. The phytochemical analysis revealed the presence of secondary metabolites such as alkaloids, steroids, terpenoids, saponins, flavonoids, tannins and phenolic compounds from the various extracts. Alkaloids were present in all the fractions tested. Methanol extracts of fruits and flowers showed the presence of major phytoconstituents. TLC profile of hexane extracts of fruits and flowers were developed using anisaldehyde sulphuric acid/ceric sulphate (steroids/terpenoids) and Dragendorff’s spray reagents (alkaloids). Petroleum ether: Chloroform: Methanol (5: 4.5: 0.5) showed good resolution for the hexane extracts of fruit and flower when treated with Dragendorff’s spray reagent. Petroleum ether: Chloroform (1:1) was best for the hexane exacts of flowers and fruits when sprayed with ceric sulphate spray reagent.